Synthesis and Crystal Structure of a [(Phen)3Mn]Ni(CN)4 - BI, JIAN-HONG; WANG, HONG-LIANG; HUANG, ZI-XIAN; HU, NAI-LIANG; KONG, LING-TAO (Asian Journal of Chemistry, 2010)
A novel complex [(Phen)3Mn]Ni(CN)4 where phen is 1,10-phenanthroline, was synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal is monoclinic, space group P2(1)/n with unit cell parameters: a = 10.46930 (10) Å, b = 20.9570 (3) Å, c = 17.07300 (10) Å, α = 90º, β =96.7380 (10)º, γ = 90º, V = 3720.03 (7) Å3, Z = 4, Mr = 812.39, Dc = 1.451 Mg/cm3, μ = 0.899 mm-1, F(000) = 1668, T = 293 ± 2 K, R = 0.0763, wR = 0.1741 for 6535 reflections with I > 2σ(I). The crystal structure analysis shows that the manganese(II) is a six-coordinated in a slightly distorted octahedron environment, then complex forms layer structure and packs in 3-D net structure through hydrogen bonds and π-π stacking interactions.